The Effect of Inlet Blade Angle Variation on Cavitation Performance of a Centrifugal Pump: A Parametric Study - Donmez, Aydin Haci; Yumurtaci, Zehra; Kavurmacioglu, Levent (ASME, 2019)
The aim of the current study is to investigate the effect of inlet blade angles on cavitation performance in a centrifugal pump. In order to reveal this relationship, both hub and shroud blade angles are considered and a two-phase three-dimensional computational fluid dynamics (CFD) study is carried out. Shear stress transport (SST) turbulence and Rayleigh-Plesset cavitation models are used in simulations. Inlet blade angles for both hub and shroud are changed and pump performance (head-discharge) and cavitation (head-inlet pressure) graphs are obtained for eight different designs. Afterward, numerical cavitation tests are conducted, required net positive suction head values of the each design are calculated, and variations are demonstrated. Results show that hub and shroud blade angle variations have no significant effect on the pump characteristic curves excluding for shroud blade angle at high discharge values. However, cavitation performance of the pump is excessively affected for both hub and shroud blade angle alterations. Increasing hub blade angle has slightly negative effect on cavitation performance of the pump. On the other hand, while increasing shroud blade angle from 20 deg to 30 deg have positive effect on cavitation performance, it is negatively affected from 30 deg to 50 deg.
Keywords: LEADING-EDGE CAVITATION; NUMERICAL-SIMULATION; FLOW; IMPELLER; PASSAGE; MODEL; Engineering